The Role of Personal Traits in Shaping Entrepreneurial Success - Asadullaev, Iskandar (Journal of Business Management, 2025)
Entrepreneurship is more than starting business-it is about people who turn ideas into reality an projects and create history.Behind every succesful entrepreneurs have traits that guie them during their life.This paper analyses 5 personality traits : risk-taking, creativity, flexibility,resilience- that shape succesful career.This charactristics are analyzed in the context how they help entrepreneurs navigate uncertainty , buil creative solutions and economic growth. By highlighting these traits, the study emphasizes their importance not only for business success but also for broader social and economic development.